NEW POTENTIAL ANTIPLASMODIAL DRUGS FROM ALSEODAPHNE SPECIES: ALSEODAPHNE PENDULIFOLIA AND ALSEODAPHNE PEDUNCULARIS - NAFIAH, MOHD AZLAN (Universiti Pendidikan Sultan Idris, 2013)
Two species from Lauraceae family; Alseodaphne pendulifolia Gamb. (KL 5732) and Alseodaphne peduncularis (Wall. ex Nees) Meisn (KL 5165) were collected from I-Iutan Simpang Lenggor, Mersing, Johor and Kluang-Mersing, Johor, respectively. Phytochemical study on these species involves extraction, separation by using various chromatographic methods and structural elucidation by spectroscopic techniques such as nuclear magnetic resonance (NMR), including I D-NMR (11-1, I3C and DEPT), 2D-NMR (COSY, HMQC/I-ISQC, and I-IMBC). Comparison with previous work were also used in elucidated the compounds structure. Five compounds were successfully isolated from Alseodaphne pendulifolia; norisocorydine N-oxide 22, corydine 23, N-mcthylhernaginc 24, oxohernagine 25 and hernagine 26 and three compounds from Alseodaphne peduncularis; boldine 27, norlirioferine 28, norboldine 29. Preliminary screening on alkaloids crude extract from these species exhibited antiplasmodial activity 0.8041lg/ml ICso and 2.135 ug/ml 1Cso against Plasmodium Jalciparum, K I isolate (resistant strain) for Alseodaphne pendulifolia and Alseodaphne peduncularis, respectively. Further investigations on isolated compounds were found to possess anti plasmodial activity (0.404 - 2.2281lg/ml ICso). Corydine 23 and oxohernagine 25 from Alseodaphne pendulifolia shows the potent results 0.404 ug/ml 1Cso and 0.738 ug/ml ICso, respectively that is active against PlasmodiumJalciparum, K I isolate (resistant strain), while the others compounds arc good to moderate active activity.